La Trata De Personas Con Fines De Explotación Sexual, Y Su Impacto Psicosocial En Las Ciudades De Ambato, Guaranda Y Riobamba En El Año 2009 - Brito Mosquera, María Fernanda (2011)
Is an undeniable reality that currently live countless social phenomena that affect global coexist, one of them is human trafficking, which has consequences in the areas: social, political, economic and cultural. The interest in mitigating the effects produced led States to recognize the situation and seek to improve the conditions in which they are produced that has such strong implications that feels as well as the movements and organizations fighting for the welfare of victims of exploitation sexual, especially for women who seek welfare for economic situations outside of their nations, workforce that is often subject to exclusion, discrimination and exploitation risk which makes them vulnerable. One of the alternatives for change in this situation is the development of national policies and takes effective guarantee of human rights in the countries of origin, transit and destination of people. Human trafficking is a phenomenon that dates back many centuries, formerly known as white slavery in the times of slavery, because of dealing with white women, is now known as a modern form of slavery in which It is negotiating with people being one chain moving inside and outside the country subjecting them to exploitation and other illegal purposes. Colombia is the main supplier in Central America for the crime of human trafficking, while Ecuador serves as a destination for the victims but also to the internal daily new cases caused by this crime occur. Human trafficking has become the second most profitable illegal business after drug trafficking, being a human rights violation affecting more than two million people. For the present investigation by the study of women and children, considered vulnerable group within the trafficked persons it was decided. It is the key role of information, because who knows her rights and that protected and where to go, can exercise their rights and enforce laws concerning the criminal code. In this sense an element contributing information to be true to the respect and enjoyment of the rights and freedoms we have as human, equal and worthy, necessary beings to live in harmony becomes. For a better understanding of the content of this study, we began introducing chapters I, II, III, making a theoretical, conceptual and contextual elements that are part of the phenomenon studied in this paper the history reference, human rights and trafficking. Chapter IV and V, presentation and discussion of results, conclusions and recommendations proposal explained; how in practice the issue of human trafficking and what happens in reality is addressed, which she gave us the elements to put together a proposal that promotes the rights approach; the conclusions and recommendations provide guidelines to consider political and social rehabilitation activities for this group of people living such a complex reality.